On the implementation of an automated acoustic output optimization algorithm for subharmonic aided pressure estimation - Dave, J. K. (2013)
Incident acoustic output (IAO) dependent subharmonic signal amplitudes from ultrasound contrast agents can be categorized into occurrence, growth or saturation stages. Subharmonic aided pressure estimation (SHAPE) is a technique that utilizes growth stage subharmonic signal amplitudes for hydrostatic pressure estimation. In this study, we developed an automated IAO optimization algorithm to identify the IAO level eliciting growth stage subharmonic signals and also studied the effect of pulse length on SHAPE. This approach may help eliminate the problems of acquiring and analyzing the data offline at all IAO levels as was done in previous studies and thus, pave the way for real-time clinical pressure monitoring applications. The IAO optimization algorithm was implemented on a Logiq 9 (GE Healthcare, Milwaukee, WI) scanner interfaced with a computer. The optimization algorithm stepped the ultrasound scanner from 0 to 100 % IAO. A logistic equation fitting function was applied with the criterion of minimum least squared error between the fitted subharmonic amplitudes and the measured subharmonic amplitudes as a function of the IAO levels and the optimum IAO level was chosen corresponding to the inflection point calculated from the fitted data. The efficacy of the optimum IAO level was investigated for in vivo SHAPE to monitor portal vein (PV) pressures in 5 canines and was compared with the performance of IAO levels, below and above the optimum IAO level, for 4, 8 and 16 transmit cycles. The canines received a continuous infusion of Sonazoid microbubbles (1.5 μl/kg/min; GE Healthcare, Oslo, Norway). PV pressures were obtained using a surgically introduced pressure catheter (Millar Instruments, Inc., Houston, TX) and were recorded before and after increasing PV pressures. The experiments showed that optimum IAO levels for SHAPE in the canines ranged from 6 to 40 %. The best correlation between changes in PV pressures and in subharmonic amplitudes (r = -0.76; p = 0.24), and between the absolute PV pressures and the subharmonic amplitudes (r = -0.89; p < 0.01) were obtained for the optimized IAO and 4 transmit cycles. Only for the optimized IAO and 4 transmit cycles did the subharmonic amplitudes differ significantly (p < 0.01) before and after increasing PV pressures. A new algorithm to identify optimum IAO levels for SHAPE has been developed and validated with the best results being obtained for 4 transmit cycles. The work presented in this study may pave the way for real-time clinical applications of estimating pressures using the subharmonic signals from ultrasound contrast agents.